Digital image of sports mega-events in the media and social networks - Belov A.A.; Bondareva A.Yu.; Lantsev A.O.; Narkhova E.N. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to analyze the “digital trail” of the International University Sports Festival in Yekaterinburg to determine the factors that form a positive image of future sports mega-events. Methods and structure of the study. During the study, mass interviews of volunteer candidates and content analysis of publications of materials about the Festival in the media and on social networks were carried out. Basic indicators of interviewing: experience and resources for participation in volunteer projects, amount of knowledge about sports mega-events, motivation for participation. Basic indicators of content analysis: number of publications about the Festival, level of publications, tone of publications. Results and conclusions. The effectiveness of a sports mega-event as a soft power largely depends on its presentation in the digital space. When assessing the digital image of a sporting mega-event, the problem is often that the positive tone of official government and official media assessments does not always match the tone of assessments given by non-state media and citizens on social networks. Along with the optimal number of official messages, the “tone” of the individual publications of the organizing participants is of great importance. One of the important transmitters of a positive image are sports volunteers.